2007
DOI: 10.1080/13632750601135881
|View full text |Cite
|
Sign up to set email alerts
|

A small‐scale study on student teachers' perceptions of classroom management and methods for dealing with misbehaviour

Abstract: The purpose of this study is to identify student teachers' perceptions of classroom management and methods for dealing with misbehaviour. In-depth interviews with nine student teachers at Ç ukurova University (Ç Ü ) in Turkey have been conducted twice, prior to and at the end of their teaching practice. Instructional management, behaviour management, communication, and physical organization of classrooms are the main components of classroom management for student teachers. Student teachers usually tend to use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
48
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 14 publications
9
48
0
1
Order By: Relevance
“…Merrett and Wheldall (1993) interviewed 176 teachers and found that while they considered classroom management skills important, approximately three-quarters were dissatisfied with the training they had received in this area, a finding confirmed in more recent studies (Atici, 2007;Giallo & Little, 2003). It is not only the student teachers who believe that they are inadequately trained in this area.…”
Section: Literature Reviewsupporting
confidence: 57%
See 1 more Smart Citation
“…Merrett and Wheldall (1993) interviewed 176 teachers and found that while they considered classroom management skills important, approximately three-quarters were dissatisfied with the training they had received in this area, a finding confirmed in more recent studies (Atici, 2007;Giallo & Little, 2003). It is not only the student teachers who believe that they are inadequately trained in this area.…”
Section: Literature Reviewsupporting
confidence: 57%
“…Notwithstanding the importance of effective behaviour management training, many student and beginning primary teachers report feeling inadequately trained to deal with student misbehaviour (Atici, 2007;Giallo & Little, 2003;Houston & Williamson, 1993). Merrett and Wheldall (1993) interviewed 176 teachers and found that while they considered classroom management skills important, approximately three-quarters were dissatisfied with the training they had received in this area, a finding confirmed in more recent studies (Atici, 2007;Giallo & Little, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As well as overviews of models of CBM, specific strategies arising from the effective teacher research (see, for example, Doyle, 1986) have been reported in teacher preparation programs (Kaufman & Moss, 2010). Specific skills such as rule development and reminders, praise, desists and redirections, ignoring, providing choices, and reinforcement of positive behaviours have been reported (Atici, 2007;Higgins & Moule, 2009;Morales, 2001;Sanderson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Atici (2007) suggested that separate (stand-alone) classroom management units were offered in recent Turkish teacher preparation programs, but no specific institutions or courses were discussed. Others have reported on semester-long methods units in classroom management for undergraduate elementary teachers (Sanderson, 2004;Stough, Montague, Landmark, & Williams-Diehm, 2006) and education majors (Clement, 2002) in the US.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation